The Cape Town Philharmonic Orchestra's Youth Development & Education Programme and its contribution to transformation and diversity within the CPO - Lesch, Odile Marissa (Stellenbosch : Stellenbosch University, 2017)
Thesis (MMus)--Stellenbosch University, 2017.